Intraocular foreign body injury in children: clinical characteristics and factors associated with endophthalmitis. Issue 6 (25th September 2019) - Yang, Yao; Yang, Chengcheng; Zhao, Ruijuan; Lin, Lixia; Duan, Fang; Lou, Bingsheng; Yuan, Zhaohui; Lin, Xiaofeng
Abstract : Background/Aims: To analyse the clinical characteristics of intraocular foreign body (IOFB) injury in children and evaluate factors associated with endophthalmitis development. Methods: Patients aged <18 years with IOFB attending Zhongshan Ophthalmic Center between January 2003 and July 2016 were included retrospectively. Demographic features, clinical characteristics and factors associated with endophthalmitis development were analysed. Results: Consecutive subjects (n=484, 484 eyes) were included: mean age 10.12±4.54 years, 86.4% male. Fireworks (28.5%) were the most common cause of injury. Injury of uncertain cause (17.5%), fireworks (36.7%) and metal splatter (31.7%) accounted for most injuries in the 0–3, 4–12 and 13–17 years age groups, respectively. Plant branches (16.7%) and fireworks (31.1%) were the most common causes of injuries in females and males, respectively. Endophthalmitis occurred in 116 patients (24.0%), with metallic IOFB (OR=0.338, p=0.001), intraocular haemorrhage (OR=0.100, p<0.001) and uveal tissue prolapse (OR=0.206, p<0.001) conferring lower risk, while zone II wound (OR=4.336, p<0.001) and traumatic lens rupture (OR=2.567, p=0.028) were associated with higher risk. Conclusion: Clinical characteristics of children with IOFB injury differ from those of adults. Fireworks are the most common cause of injury, indicating a ban on children igniting fireworks should be advocated. Safety education and protective measures should vary by age and sex. Endophthalmitis is associated with zone II wound, traumatic lens rupture, IOFB material, intraocular haemorrhage and uveal tissue prolapse, which has clinical relevance.